Analysis of Design of Ultra-Low-Power Sensor Nodes for IOT Applications: Advancements in Wireless Sensor Nodes for Energy-Efficient IoT Applications (Journal of Advances and Scholarly Researches in Allied Education, 2020)
The expanding interest for Wireless Sensor Nodes (WSNs) ready to collect and transmit information through wireless communication channels, while frequently situated in areas that are hard to access, is driving investigation into imaginative solutions including energy harvesting (EH) and wireless power transfer (WPT) to in the end permit sans battery sensor hubs. Because of the inescapability of radio frequency (RF) energy, RF EH and WPT are key technology with the possibility to control IoT devices and brilliant detecting designs including hubs that should be wireless, upkeep free, and adequately low in cost to advance their utilization anyplace.